Effect of Ergonomic Practices on Computer Vision Syndrome (CVS) symptoms among undergraduate and postgraduate IT students of University of Chakwal: Effect of Ergonomic Practices on CVS symptoms - Jabeen, Shajeea; Khalid, Mehreen; Shahid, Rizwana; Khalil, Iqra; Haider, Sajjad; Jamil, Ushana (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Computer Vision Syndrome (CVS) is common nowadays among students due to constant working on computer. In addition to various visual and ocular disorders, there is also periodic rise in their musculoskeletal problems. Objective: To determine the effect of visual ergonomics on CVS among IT university students of Chakwal. Methods: A cross-sectional descriptive study was done in IT department of the University of Chakwal from October-December 2021. About 65 undergraduate and postgraduate IT students studying in the University of Chakwal were enrolled through consecutive sampling. Students using computers and having symptoms of Computer Vision Syndrome (CVS), refractive error and convergence insufficiency were included. The data were gathered for visual effects in response to different ergonomics and was analysed by SPSS 25.0 and Microsoft Excel 2016. P ≤0.05 was taken as significant. Results: Of the 65 students, most (72.3%) were undergraduate students. Almost 55.4% complained of severe neck / shoulder pain and dryness of eyes. 39% used to do computer work for 1-4 hours / day. Students working for 1-4 hours at home had less blinking and watering of eyes in addition to eyestrain (p< 0.05). There was significant association of mild headache (p<0.02) and minimal photophobia (p<0.05) with 1-4 hours computer work at home. Taking break up to 1 hour had significant association with mildness of eye burning, crossing and redness (p<0.05). Conclusions: IT students had moderate to severe dryness of eyes, neck and shoulder pain. Not spending more than four consecutive hours on computer work and taking at least one hour break is imperative to avoid severe symptoms